Impact of Xanthylium Derivatives on the Color of White Wine - Franziska Bührle; Anita Gohl; Fabian Weber (Molecules, 2017)
Xanthylium derivatives are yellow to orange pigments with a glyoxylic acid bridge formed by dimerization of flavanols, which are built by oxidative cleavage of tartaric acid. Although their structure and formation under wine-like conditions are well established, knowledge about their color properties and their occurrence and importance in wine is deficient. Xanthylium cations and their corresponding esters were synthesized in a model wine solution and isolated via high-performance countercurrent chromatography (HPCCC) and solid phase extraction (SPE). A Three-Alternative-Forced-Choice (3-AFC) test was applied to reveal the color perception threshold of the isolated compounds in white wine. Their presence and color impact was assessed in 70 different wines (58 white and 12 rosé wines) by UHPLC-DAD-ESI-MSn and the storage stability in wine was determined. The thresholds in young Riesling wine were 0.57 mg/L (cations), 1.04 mg/L (esters) and 0.67 mg/L (1:1 (w/w) mixture), respectively. The low thresholds suggest a possible impact on white wine color, but concentrations in wines were below the threshold. The stability study showed the degradation of the compounds during storage under several conditions. Despite the low perception threshold, xanthylium derivatives might have no direct impact on white wine color, but might play a role in color formation as intermediate products in polymerization and browning.